The Role And Improvement Of The Setter’s Ability In Volleyball - Ekxael Pasaribu; Lidia Medianti BR Surbakti; Rabyatul Adawiyah; Ghazi Al Ghifari; Cello Pradana (STAMINA, 2025)
This study aims to analyze in depth the role of the setter in enhancing volleyball performance from technical, tactical, and communication perspectives. The research employed a qualitative descriptive approach through library research by synthesizing findings from seven relevant national and international scientific journals. The results show that the setter holds a central position as the main playmaker who directs attacks and controls the game’s tempo. Technically, the setter’s accuracy in overhead passing, precision of ball distribution, and coordination between vision and hand movement are crucial factors determining team effectiveness. Training using setter training balls has been proven to significantly improve passing accuracy and ball control. Moreover, the use of supporting tools such as the smash-setter device strengthens the cooperation between the setter and the spiker, resulting in faster and more varied attack patterns. From a tactical perspective, setters must be able to read game situations and make rapid, accurate decisions according to the opponent’s defense conditions. Meanwhile, verbal and nonverbal communication plays an essential role in maintaining coordination among players during the dynamic flow of matches. The combination of technical proficiency, tactical intelligence, and communication ability makes the setter the “brain of the game,” determining the team’s success. Therefore, the development of setter skills should be carried out comprehensively through integrated training that includes technical, tactical, psychological, and communication aspects to produce adaptive, strategic, and competitive players at various levels of competition